Behaviour of fibre-reinforced cementitious composite containing high-volume fly ash at elevated temperatures - Mo, Kim Hung; Loh, Zhi Pin; Tan, Chee Ghuan; Alengaram, Ubagaram Johnson; Yap, Soon Poh (Springer, 2018)
This research describes the properties of acrylic fibre-reinforced cementitious composite containing high-volume fly ash. In this investigation, the fly ash content (30% and 60%) and the acrylic fibre dosage (0%, 1% and 2%) were varied. Increased content of fly ash in the composite was found to be able to partially compensate the reduction in workability caused by the inclusion of fibres. On the other hand, although the use of fibres had minimal influence on the compressive strength, the fibres could significantly enhance the flexural strength of the composite, particularly in the composite containing higher fly ash content. At elevated temperatures, it was found that the inclusion of acrylic fibres was beneficial in the composite with higher fly ash content, as demonstrated by the increased strength retention and reduced spalling damage at elevated temperature.